The incorporation of small cations in hydroxyapatite : synthesis, crystal chemistry and functionality - Low, Hou Ran (2012)
Hydroxyapatite (HAp) is an important oxide in biotechnology, and also holds promise as a heterogeneous catalyst. Its ideal composition is [(CaF4)(CaT6)(PO4)6(OH)2] where an adaptable framework (F) structure creates one-dimensional tunnels (T) that provide multiple ionic acceptor sites (CAF/CAT/P/OH) which can be adjusted to deliver specific functionality. Modification of cation and anion type and proportions, together with selection of appropriate syntheses, can be used to regulate structural distortions and phase transformation. However, first-principles crystallographic adaptation to optimize performance is less explored, especially for tailoring excipients responses and catalytic activity, which are the primary concern of this study.